Do Electronic Health Records Affect Quality of Care? Evidence from the HITECH Act - Lin, Yu-Kai; Lin, Mingfeng; Chen, Hsinchun (Information Systems Research, 2019)
The 2009 Health Information Technology for Economic and Clinical Health (HITECH) Act is landmark legislation that places electronic health record (EHR) technologies at the center of health system reform in the United States. This study leverages the meaningful use (MU) provisions of the HITECH Act to quantify different degrees of EHR use in a large and heterogeneous set of hospitals and investigates the impact of EHR use on quality of care. The results provide evidence of EHRs’ positive quality effects and reconcile earlier mixed findings in the EHR evaluation literature by showing that their benefits vary according to different levels of use and hospital characteristics. The effect sizes were larger in disadvantaged (i.e., small and rural) hospitals, suggesting the potential of EHRs in mitigating the disparities in the quality of healthcare.